2022
DOI: 10.1186/s12866-022-02626-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological characteristics of different tongue coatings in adults

Abstract: Background Tongue coating is an important health indicator in traditional Chinese medicine (TCM). The tongue coating microbiome can distinguish disease patients from healthy controls. To study the relationship between different types of tongue coatings and health, we analyzed the species composition of different types of tongue coatings and the co-occurrence relationships between microorganisms in Chinese adults. From June 2019 to October 2020, 158 adults from Hangzhou and Shaox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Second, there are many tongue image feature types, as shown in Figure 1 , and they are more likely to be comprehensively judged as the probability of a certain type of health state. 10 , 121 The health state abstracted from the whole body system is related to the concept of “syndrome.” TCM theory believes that the human body is an interrelated system, the running state and abnormal symptoms of different body parts are interrelated and mutually affected, 1 , 122 showing a certain distribution law, and syndrome types could be treated as the clusters summarized by this distribution. Therefore, not only do the features of the tongue image need to be integrated but also the features from other diagnostic methods, to better distinguish syndromes.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there are many tongue image feature types, as shown in Figure 1 , and they are more likely to be comprehensively judged as the probability of a certain type of health state. 10 , 121 The health state abstracted from the whole body system is related to the concept of “syndrome.” TCM theory believes that the human body is an interrelated system, the running state and abnormal symptoms of different body parts are interrelated and mutually affected, 1 , 122 showing a certain distribution law, and syndrome types could be treated as the clusters summarized by this distribution. Therefore, not only do the features of the tongue image need to be integrated but also the features from other diagnostic methods, to better distinguish syndromes.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…TCM physicians rely heavily on it as they obtain the whole human health state through it, so they arrange the herbs to balance the body's health state. Because of the abundant superficial vascular tissue, the tongue can transmit many useful signals in real time, 1 3 which may indicate important medical information. Nowadays, tongue diagnosis can even be used for disease prediction or disease stage estimation.…”
Section: Introductionmentioning
confidence: 99%
“…In studies examining tongue-coating microbes, fusobacterium periodonticum , neisseria mucosa , and aggregatibacter segnis were associated with tongue coating ( 86 ). The Extended Human Oral Microbiome Database (eHOMD) was updated in 2017 and found that six major phyla including Firmicutes , Actinobacteria , Proteobacteria , Fusobacteria , Bacteroidetes and Spirochetes , constitute 96% of total oral bacteria ( 87 ).…”
Section: Oral Microbiome Halitosis and Periodontitismentioning
confidence: 99%